The Security Issue of The Cyprus Problem - Klokkaris, Phivos (Études helléniques / Hellenic Studies, 2011)
The author defines the Security issue of the Cyprus Problem in its proper dimension. He argues that security is a prerequisite to peace, freedom and democracy. The long term stability of the region depends on the application of this principle in equal measure to Cyprus as to all the states of the region.